Minimum recombination histories by branch and bound - Lyngso, R; Song, Y; Hein, J (2005)
Recombination plays an important role in creating genetic diversity within species, and inferring pasi recombination events is central to many problems in genetics. Given a set M of sampled sequences, finding an evolutionary history for M with the minimum number of recombination events is a computationally very challenging problem. In this paper, we present a novel branch and bound algorithm for-tackling that problem. Our method is shown to be far more efficient than the only preexisting exact method, described in [1], Our software implementing the algorithm discussed in this paper is publicly available. © Springer-Verlag Berlin Heidelberg 2005.